2021
DOI: 10.3390/cancers13051158
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Snail by DUSP1 Impairs Cell Migration and Invasion through the Inactivation of JNK and ERK and Is Useful as a Predictive Factor in the Prognosis of Prostate Cancer

Abstract: Dual specificity phosphatase 1 (DUSP1) is crucial in prostate cancer (PC), since its expression is downregulated in advanced carcinomas. Here, we investigated DUSP1 effects on the expression of mesenchymal marker Snail, cell migration and invasion, analyzing the underlying mechanisms mediated by mitogen-activated protein kinases (MAPKs) inhibition. To this purpose, we used different PC cells overexpressing or lacking DUSP1 or incubated with MAPKs inhibitors. Moreover, we addressed the correlation of DUSP1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…As shown in Figure 4A, there was no change in p38 and JNK signaling pathway, indicating a specific relationship with the ERK/MARK pathway. According to the previous studies, DUSPs can inactivate ERK1, 2 by dephosphorylating residues required for catalytic activity (Chappell et al, 2013;Ramkissoon et al, 2019;Martínez-Martínez et al, 2021). Then we selected the differential genes DUSP3/DUSP4/DUSP6 related to ERK dephosphorylation in the ERK/MAPK pathway and performed RT-qPCR to examine the expression of DUSP3/DUSP4/DUSP6 in control and hnRNPA2B1-KO cell lines.…”
Section: Hnrnpa2b1 Promotes the Development Of Colon Cancer By Regulating The Erk/mapk Pathwaymentioning
confidence: 99%
“…As shown in Figure 4A, there was no change in p38 and JNK signaling pathway, indicating a specific relationship with the ERK/MARK pathway. According to the previous studies, DUSPs can inactivate ERK1, 2 by dephosphorylating residues required for catalytic activity (Chappell et al, 2013;Ramkissoon et al, 2019;Martínez-Martínez et al, 2021). Then we selected the differential genes DUSP3/DUSP4/DUSP6 related to ERK dephosphorylation in the ERK/MAPK pathway and performed RT-qPCR to examine the expression of DUSP3/DUSP4/DUSP6 in control and hnRNPA2B1-KO cell lines.…”
Section: Hnrnpa2b1 Promotes the Development Of Colon Cancer By Regulating The Erk/mapk Pathwaymentioning
confidence: 99%
“…As several of these studied signaling pathways are also involved in cell migration[ 46 ], we then decided to study this process. As shown in Figure 2 , we observed that PTHrP enhances the motility of CRC-derived cell lines[ 40 ].…”
Section: Pthrp Promotes Cell Cycle Progression Proliferation and Migration Of Crc Cellsmentioning
confidence: 99%
“…More recently, it has been shown that TRβ is also able to limit the CSCs population in breast cancer by decreasing, not only their self-renewal capacity, but also the efficiency of mammosphere formation as well as the expression of pluripotency factors ( 114 ). Different reports have demonstrated that mammospheres are enriched in EMT markers such as the transcription factor Snail ( 115 117 ), which is constitutively upregulated in a wide variety of tumors ( 118 ), including prostate cancer ( 119 ), where NF-kB and p38MAPK signaling pathways play important roles ( 46 ). Despite this, TRβ increases Snail expression in mammospheres, suggesting that the effects of T3 on CSC biology are not related to EMT changes ( 114 ).…”
Section: Introductionmentioning
confidence: 99%